Working from Home Increases Work-Home Distances - Sena Coskun; Wolfgang Dauth; Hermann Gartner; Michael Stops; Enzo Weber (Institute of Labor Economics (IZA), 2024)
This paper examines how the shift towards working from home during and after the Covid-19 pandemic shapes the way how labor market and locality choices interact. For our analysis, we combine large administrative data on employment biographies in Germany and a new working from home potential indicator based on comprehensive data on working conditions across occupations. We find that in the wake of the Covid-19 pandemic, the distance between workplace and residence has increased more strongly for workers in occupations that can be done from home: The association of working from home potential and work-home distance increased significantly since 2021 as compared to a stable pattern before. The effect is much larger for new jobs, suggesting that people match to jobs with high working from home potential that are further away than before the pandemic. Most of this effect stems from jobs in big cities, which indicates that working from home alleviates constraints by tight housing markets. We find no significant evidence that commuting patterns changed more strongly for women than for men.
Keywords: J61; R23; 330; working from home; commuting; urban labor markets